(untitled) (Research, Society and Development, 2022)
Introduction: On the lateral wall of each nasal cavity, there are three conchas named according to their position: superior, middle and inferior. Eventually, there may be a fourth concha (of Santorini), known as the supreme concha. However, its specific characteristics are scarce in the literature, being superficially addressed in scientific studies and textbooks. Objective: To describe the morphological aspects of the supreme concha and analyze its clinical and surgical importance. Methodology: Integrative literature review with searches in PubMed, Scopus, Web of Science, Embase and MEDLINE databases. As a search tool, the descriptors “supreme concha nasal”, “supreme turbinate” and “concha Santorini” were used, as well as the Boolean operator “or”. Eligibility criteria consisted of original articles without language and publication period restrictions. Results and Discussion: Among 21 non-duplicated articles, six were selected. The supreme concha is found more bilaterally and its prevalence varies from 10% to 77% (average of 42.3%), being predominant in males and having a higher frequency in the second trimester of intrauterine life, in addition to having a similar size to the superior concha in most cases. The knowledge of the supreme concha is important for many endoscopic surgical procedures of the sinuses and skull base. Conclusion: The supreme concha is more common than previously thought. Imaging studies in computed tomography, mainly with 3D reconstruction, revealed a higher prevalence than anatomical studies in cadavers. It is inferred that the Santorini concha may not be an anatomical variation in some populations.